Pengaruh Model Pembelajaran Problem Based Learning (PBL) Terhadap Hasil Belajar Matematika Pada Siswa Kelas V UPTD SDN Gili Barat - Siti Rahmawati; Bagus Rahmad Wijaya (Jurnal Bintang Pendidikan Indonesia, 2023)
The purpose of this study was to determine whether there was an effect of the problem-based learning model on mathematics learning outcomes in fifth grade students of UPTD SDN Gili Barat. This research is a quantitative research with the method used is quasi-experimental and the design used is nonequivalent control group design. The sample used was 45 students from fifth grade A and B of UPTD SDN Gili Barat. Sampling using saturated samples. In this study using the experimental class and control class. Data collection used multiple choice test questions, the test instruments used were validity tests, reliability tests, difficulty level tests and discrimination tests. The prerequisite test used is the normality test and homogeneity test while the hypothesis test uses the t-test. Based on the results of data analysis using the t-test with a significance level of 0.05, the results were sig. (2-tailed) of 0.010 means that Ho is rejected and Ha is accepted so that it can be concluded that there is a significant difference between the experimental group and the control group, the treatment given has a significant effect on the problem-based learning model of learning mathematics in fifth grade students of UPTD SDN West Gili.